Evaluation of Pengenalan Tipografi 2021/2022 Course’s Hybrid Learning Format - Brian Alvin Hananto (IMATYPE: Journal of Graphic Design Studies, 2022)
As limitations of the physical classes because of the COVID-19 pandemic started to subdue, Universitas Pelita Harapan attempts to conduct Pengenalan Tipografi in a hybrid learning format. To measure the effectiveness of the hybrid learning format and the syllabus’s adjustments due to the shift in format, the author conducted classroom action research to evaluate the conduct of the hybrid learning format in the 2021/2022 academic year. The data used to assess the class is a combination of qualitative and quantitative data, such as the final grades, scores of each assignment, surveys, and interviews. The study shows that the conduct of the 2021/2022 academic year is considered successful as the students receive an overall mean of B-, and 77% of the students who participated in the survey gave the hybrid format learning a 4.27 out of 5 scores.